Ceramide- and ERK-dependent pathway for the activation of CCAAT/enhancer binding protein by interleukin-1β in hepatocytes - Natalia V. Giltiay; Alexander A. Karakashian; Alexander P. Alimov; Sandy Ligthle; Mariana N. Nikolova-Karakashian (Journal of Lipid Research, 2005)
Interleukin-1β (IL-1β) is a major inducer of liver acute-phase protein expression in response to infection. Several transcription factors, including CCAAT/enhancer binding protein (C/EBP), are known mediators in this process, although the mechanisms by which they modulate IL-1β's action are not completely understood. Activation of sphingomyelinase (SMase) and the subsequent generation of ceramide are early steps in the IL-1β signaling cascade. In this study, we investigate the role of ceramide in the IL-1β regulation of C/EBP in primary hepatocytes. The C/EBP DNA binding activity was found to increase in a dose-dependent manner after stimulation with IL-1β and exogenous addition of C2-ceramide or treatment with SMase. These changes were accompanied by an increase in the nuclear content of C/EBPβ. Both IL-1β and ceramide led to extracellular signal-regulated kinase 1/2 (ERK1/2) activation as early as 15 min after treatment. Furthermore, the increase of cellular ceramide content resulted in increased phosphorylation of C/EBPβ at serine 105 at later time points. Concurrently, the cytosolic levels of C/EBPβ decreased, suggesting that IL-1β and ceramide induced nuclear translocation of C/EBPβ. Ceramide-induced C/EBPβ phosphorylation, translocation, and DNA binding were suppressed by the addition of PD98059, an inhibitor of ERK1/2 phosphorylation.These results suggest that ceramide and ERK mediate a pathway in the IL-1β signaling cascade, which results in rapid posttranslational activation of C/EBPβ.